Religiosity and trajectories of lifetime fertility intentions: evidence from a German panel study - Bein, Christoph; Passet-Wittig, Jasmin; Bujard, Martin; Gauthier, Anne Hélène (Advances in life course research, 2023)
Much of the literature on fertility intentions has shown that they are broadly predictive of fertility behaviour. Fertility intentions tend to change over a person’s life. How religiosity affects these changes over time has rarely been the subject of investigation. In this paper, we focus on whether and how religiosity affects trajectories of lifetime fertility intentions. Specifically, we examine whether highly religious people start with higher fertility intentions and are more likely to sustain them during their life course compared to their less religious counterparts. We apply random and fixed effects growth curve models to data from the German family panel pairfam, using a sample of 6214 women and 5802 men aged 14-46. We find that religiosity mainly contributes to explain the starting level at teenage years but not the trajectories of lifetime fertility intentions as people get older. Highly religious people start with higher intentions than less religious people. However, similarly to less religious people they experience a decline in their fertility intentions with age. This study demonstrates that religiosity is an important variable in research on fertility intentions but with changing relevance over the life course.